2019
DOI: 10.18203/2349-2902.isj20192985
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcome of chest trauma: a four year retrospective analysis at a tertiary care centre

Abstract: Background: Chest trauma comprises about 10-15% of all traumas and 25% of all deaths from traumatic injury. Chest injuries are cause by blunt mechanisms such as road traffic accidents or penetrating mechanisms such as stab and missile injuries. Traumatic chest injuries are the most common cause of preventive mortality and morbidity.Methods: A retrospective study of all patients with chest injury presenting to Emergency Department of SKIMS Medical College, Srinagar was done.  Records of all the patients were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…On the other hand the nding of this study is lower than the studies done in England (35.6%)(2), India(20.84%) (21) and Tanzania (24.4%)(8). The possible justi cation for being lower might be due to difference in sample size (large sample size) in the above studies.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…On the other hand the nding of this study is lower than the studies done in England (35.6%)(2), India(20.84%) (21) and Tanzania (24.4%)(8). The possible justi cation for being lower might be due to difference in sample size (large sample size) in the above studies.…”
Section: Discussioncontrasting
confidence: 83%
“…1 & 2 to get the rst participant (The number was 1). Therefore, every kth = 2nd interval study subjects (charts) were selected until the sample size of 422.The data were collected using a pre-tested and structured data extraction checklist adapted from different literature (10,11,15,21,27). The checklist was developed in English language and contains ve parts to extract relevant information such as sociodemographic characteristics of the participants, injury related factors, patient condition at admission, treatment modality related factors and co-morbid diseases.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While gunshot injuries were the main cause of penetrating chest injuries, road traffic accidents (RTA) were the main source of blunt chest injuries. Most frequently, TT was used to treat patients (65%), and conservative treatment was used to treat 28% of the patients [ 20 ]. Sikander et al (2020) found that hemothorax and hemopneumothorax were the most frequent primary presentations, with rib fracture encountered in 90% of the patients.…”
Section: Introductionmentioning
confidence: 99%